2018
DOI: 10.1021/acschembio.7b00822
|View full text |Cite
|
Sign up to set email alerts
|

A Peptidomimetic Antibiotic Interacts with the Periplasmic Domain of LptD from Pseudomonas aeruginosa

Abstract: The outer membrane (OM) in Gram-negative bacteria is an asymmetric bilayer with mostly lipopolysaccharide (LPS) molecules in the outer leaflet. During OM biogenesis, new LPS molecules are transported from their site of assembly on the inner membrane to the OM by seven LPS transport proteins (LptA-G). The complex formed between the integral β-barrel OM protein LptD and the lipoprotein LptE is responsible for transporting LPS from the periplasmic side of the OM to its final location on the cell surface. Because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
66
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 33 publications
0
66
0
2
Order By: Relevance
“…Irradiation with UV light results in the generation of highly reactive intermediates,w hich react with proximal protein groups and covalently link the probe and the protein for downstream sample preparation. [129][130][131] Recent advancements have established mass spectrometry as awidely used and very powerful tool for the analysis of cellular metabolic (metabolomics) or protein (proteomics) networks.T his includes the identification of functional pathways that are affected upon treatment with antibacterial compounds.I narecent study by Zampieri et al,anontargeted metabolomics approach was applied to monitor the immediate short-term metabolic response of E. coli to av ariety of antibiotic perturbations. [124][125][126] An illustrative recent example is the target elucidation of the Pseudomonad secondary metabolite promysalin in P. aeruginosa.…”
Section: Target Identification and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation with UV light results in the generation of highly reactive intermediates,w hich react with proximal protein groups and covalently link the probe and the protein for downstream sample preparation. [129][130][131] Recent advancements have established mass spectrometry as awidely used and very powerful tool for the analysis of cellular metabolic (metabolomics) or protein (proteomics) networks.T his includes the identification of functional pathways that are affected upon treatment with antibacterial compounds.I narecent study by Zampieri et al,anontargeted metabolomics approach was applied to monitor the immediate short-term metabolic response of E. coli to av ariety of antibiotic perturbations. [124][125][126] An illustrative recent example is the target elucidation of the Pseudomonad secondary metabolite promysalin in P. aeruginosa.…”
Section: Target Identification and Validationmentioning
confidence: 99%
“…[127] In addition to small molecules,A(f)BPP has also been applied for the target elucidation of antibacterial peptides by means of modified amino acids. [129][130][131] Recent advancements have established mass spectrometry as awidely used and very powerful tool for the analysis of cellular metabolic (metabolomics) or protein (proteomics) networks.T his includes the identification of functional pathways that are affected upon treatment with antibacterial compounds.I narecent study by Zampieri et al,anontargeted metabolomics approach was applied to monitor the immediate short-term metabolic response of E. coli to av ariety of antibiotic perturbations. [132] Thea uthors quantified changes in about 750 metabolites upon exposure to the antibiotic and could see concentration-and compoundspecific changes of distinct metabolic pathways.I mportantly, this profiling approach cannot only be used to predict the MoA of new compounds,i ta lso aids the identification of novel druggable targets,a sr ecently shown in M. tuberculosis.…”
Section: Target Identification and Validationmentioning
confidence: 99%
“…[122,123] Bei Konjugation mit einem Fluorophor-Azid werden die Zielproteine anschließend mit-tels SDS-PAGEa ufgetrennt und durch Fluoreszenz-Imaging des Gels visualisiert. [129][130][131] Die modernen Fortschritte haben die Massenspektrometrie als eine weit verbreitete und äußerst leistungsfähige Methode zur Analyse der zellulären Netzwerke von Metaboliten (Metabolomik) und Proteinen (Proteomik) etabliert. B. Biotin-Azid) angehängt wurde,k çnnen die Proteine durch Affinitätschromatographie angereichert und proteolytisch verdaut werden.…”
Section: Identifizierung Und Validierung Der Biologischen Zielstrukturunclassified
“…[127] Im Allgemeinen kann A(f)BPP nicht nur zur Zielprotein-Identifizierung von niedermolekularen Verbindungen verwendet werden, sondern auch fürdie Target-Analyse von antibakteriellen Peptiden, in die modifizierte Aminosäuren eingebracht wurden. [129][130][131] Die modernen Fortschritte haben die Massenspektrometrie als eine weit verbreitete und äußerst leistungsfähige…”
Section: Identifizierung Und Validierung Der Biologischen Zielstrukturunclassified
“…The periplasmic domain of the LptD (34-323) is 100 amino acids longer than LptD of E. coli and contains a pair of cysteine residues that could form a disulfide bond. In SDS-PAGE, heat denatured LptD with and without reduction with dithiothreitol (DTT) showed denatured and non-reduced LptD with an apparent size of 130 kDa and the DTT-reduced form with an apparent size of 100 kDa suggesting the presence of a putative interdomain di-sulfide bond(Andolina et al, 2018). Additionally, by sequential replacement of all six cysteine residues to serine and examining the gel mobility of such modified LptD in SDS-PAGE showed that the protein is of 100 kDa, suggesting the presence of internal disulfide bonds of LptD(Andolina et al, 2018).…”
mentioning
confidence: 99%